Factorial design of reactive concrete powder containing electric arc slag furnace and recycled glass powder (2020)
The main objective of this research is to develop an optimized mixture of reactive powder concrete (RPC) containing supplementary cementitious materials (SCM), such as Electric Arc Slag Furnace (EASF), and Recycled Glass Powder (RGP) among others, through a factorial design. Accurate polynomial regressions were adjusted between considered factors and obtained responses such spread flow and compressive strength at different ages of the concrete. A multi-objective algorithm was executed to reach an eco-friendly mixture with the proper flow, the highest compressive strength, while simultaneously having the minimum content of cement. The experimental verification of this mathematical optimization demonstrated that the use of 621 kg/m3 of ASTM Type HE cement, with a maximum content of 100 kg/m3 of silica fume, should be considered the most appropriate amount to be employed in the RCP mixture to achieve a value of compressive strength over 150 MPa and a self-compacting mixture.